Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/10245332.2017.1312088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of FDG–PET/CT for the evaluation of various types of adult T-cell leukemia

Abstract: FDG-PET/CT findings could be useful for clinically grading ATL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Additionally, PET/CT helps predict the prognosis of ATLL. Nakachi et al demonstrated that the intensity of FDG uptake was significantly higher in the acute and lymphoma subtypes than in the smoldering and chronic subtypes (18). The prognosis of ATLL patients with breast involvement as an extranodal site has not been assessed because of the rarity of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PET/CT helps predict the prognosis of ATLL. Nakachi et al demonstrated that the intensity of FDG uptake was significantly higher in the acute and lymphoma subtypes than in the smoldering and chronic subtypes (18). The prognosis of ATLL patients with breast involvement as an extranodal site has not been assessed because of the rarity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The monoclonal integration of HTLV-1 proviral DNA in the blood was confirmed by southern blotting. 18 F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) demonstrated an increased FDG uptake, not only in the skin nodules, but also in the bilateral breasts with standardized uptake values of 10.6 and 12.9, respectively (Fig. 1).…”
Section: Case Reportmentioning
confidence: 99%
“…However, it may indicate the limitation of evaluating treatment response only in terms of morphology. The previous study reported the clinical usefulness of FDG-PET for evaluating ATL; as such, FDG-PET may be able to predict whether ATL lesions will have tumor regrowth after RT [22].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown FDG-PET to be a powerful modality for assessing hematological malignancies and other neoplastic diseases [44][45][46][47]. In a retrospective study evaluating the utility of FDG-PET in diagnosing, staging, and restaging primary splenic lymphoma, 96.2% sensitivity, 91.7% specificity, and 94% accuracy were reported [48].…”
Section: Malignancymentioning
confidence: 99%